SINONIM NOMINA BAWINE ‘PEREMPUAN’ DALAM BAHASA SANGIR - Kasiahe, Evi Martika D. (Universitas Sam Ratulangi, 2018)
The problem of synonymous words is one of the focuses of semantic study with a complex set of analyzes. In addition to the semantic studies of synonymous semantics is also an important issue, the use of the word has the same meaning sometimes used inappropriately and even erroneously because of lack of understanding of the lexical meaning that is synonymous. This research focuses on the synonyms of bawine nouns in Sangirese language. The purpose is to identify the distinguishing features on the synonyms of bawine nouns in Sangirese language and identify the scope of the use of words which include the bawine noun synonym pair in the Sangirese language. Primary data source used in this research is informant which is native speaker of Sangirese language. This research uses component analysis technique of meaning (componential analysis). After analysis, it is found that in the bawine nouns in Sangirese language only three words are close synonym while the other words are only hyponimic, yet there is a general semantic characteristic that applies between these noun pairs. Some words that are grouped into the synonyms of noun bawine, are actually just hyponimic and not synonymous Keywords: synonymous nouns, components of meaning, Sangirese language